Incidence of balanitis xerotica obliterans in boys younger than 10 years presenting with phimosis - Kühhas, Franklin; Miernik, A.; Weibl, P.; Schoenthaler, M.; Sevcenco, S.; Schauer, I.; Tosev, Georgi; Oezsoy, M.; Lassmann, J. (Urologia internationalis, 2013)
Objective: Evaluation of the true incidence of balanitis xerotica obliterans (BXO) among boys younger than 10 years. Methods: In a period of 13 months, 75 boys younger than 10 years were treated for phimosis. Suspicion of BXO was raised in phimosis grade 2 or 3 (classification by Kikiros). Patients were offered primarily either circumcision or conservative therapy and circumcision secondarily (if treatment failed in the conservative group). Each circumcision specimen was examined histopathologically. Results: Circumcision was primarily performed in 29 and secondarily in 17 patients. The mean age was 3.7 years (range 1-10). BXO, chronic inflammation, and normal histological results were found in 8/26/12 (17.4/56.5/26.1%) cases, respectively. The mean follow-up was 8.1 months. No recurrences were reported. Conclusions: The incidence of BXO appears to be higher than previously reported. The clinical appearance in children may be confusing. The preoperative BXO suspicion did not correlate with the final histopathological results.
Published online: December 29, 2012
Gesehen am 28.06.2021